Clinical response to biologicals for severe asthma: any relevance for sex in different age ranges?. Issue 3 (18th July 2022) - Benoni, Roberto; Panunzi, Silvia; Batani, Veronica; Moretti, Francesca; Fuggini, Stefano; Todesco, Mattia; Senna, Gianenrico; Poli, Albino; Vianello, Andrea; Caminati, Marco
Background: Whether sex can influence the clinical response to biological treatment in patients with severe asthma has not been fully addressed. Aims and methods: The aim of this study was to investigate in patients with severe asthma undergoing biological treatment the individual evolution of lung function measurements and patient-reported asthma control scores over a 12-month follow-up period, in relation to patients' sex, in different age ranges. Second, the change in the administered dose of oral corticosteroids (OCS) before and after 12 months of treatment was investigated. Results: 64 patients (58% female and 42% male) with a median age of 52 years were enrolled in the study. There were no relevant differences between sexes in terms of lung function, patient-reported asthma control, exacerbation rate and daily OCS dose within the study timeframe. A separate sub-analysis by biological treatment confirmed the same finding. Stratifying individuals by age, we showed that older men had lower lung function parameter values (forced expiratory volume in 1 s (FEV1 ) % predicted and FEV1 /forced vital capacity index) than older women, whereas an opposite trend was observed in terms of Asthma Control Test score. No other relevant differences were detected after age stratification. Conclusion: According to our findings, sex does not act as a determinant of treatment response to biologicals in people with severe asthma. Although to be confirmed in larger studies, our data suggest that neither sex nor age should limit biological treatment prescription, once the eligibility criteria for that therapy are satisfied. Sex does not seem to act as a determinant of treatment response to biologicals in severe asthma. Neither sex nor age should limit biological treatment prescription, once the eligibility criteria for that therapy are satisfied. https://bit.ly/370frEP